Exercise modulates redox-sensitive small GTPase activity in the brain microvasculature in a model of brain metastasis formation. - Gretchen Wolff (Public Library of Science (PLoS), 2014)
Tumor cell extravasation into the brain requires passage through the blood-brain barrier (BBB). There is evidence that exercise can alter the oxidation status of the brain microvasculature and protect against tumor cell invasion into the brain, although the mechanisms are not well understood. In the current study, we focused on the role of microenvironment generated by exercise and metastasizing tumor cells at the levels of brain microvessels, influencing oxidative stress-mediated responses and activation of redox-sensitive small GTPases. Mature male mice were exercised for four weeks using a running wheel with the average voluntary running distance 9.0 ± 0.3 km/day. Mice were then infused with 1.0 × 10(6) D122 (murine Lewis lung carcinoma) cells into the brain microvasculature, and euthanized either 48 hours (in short-term studies) or 2-3 weeks (in long-term studies) post tumor cell administration. A significant increase in the level of reactive oxygen species was observed following 48 hours or 3 weeks of tumor cells growth, which was accompanied by a reduction in MnSOD expression in the exercised mice. Activation of the small GTPase Rho was negatively correlated with running distance in the tumor cell infused mice. Together, these data suggest that exercise may play a significant role during aggressive metastatic invasion, especially at higher intensities in pre-trained individuals.